Brown algae (Phaeophyceae) stressors and illnesses: a review for a sustainable aquaculture under climate change - Ruiz Martínez, Eliana; Schroeder, Declan C.; Thuestad, Gunnar; Hoell, Ingunn A. (Frontiers in Aquaculture, 2024)
Brown algae (Phaeophyceae) dominate intertidal and shallow subtidal areas globally, where larger species form extensive underwater forests. These structurally complex and highly productive habitats enhance local biodiversity and support food webs in coastal areas through secondary production, thereby shaping local oceanography and ecology. Macroalgal aquaculture is an important and growing sector, where approximately 40% of all cultivated algae belong to Phaeophyceae. However, both cultured and natural brown algae have been under increasing pressure due to climate-driven factors, such as ocean warming, eutrophication, and herbivore outbreaks. We conducted a comprehensive literature review on abiotic (temperature, light intensity, and UV radiation, nutrients, water motion, salinity, and substrata and sediment) and biotic (bacteria, viruses, fungi, eukaryotic endophytes and endoparasites, epiphytes, and grazers) stressors and illnesses in marine brown macroalgae, as well as brown algae defense mechanisms, and discuss how these parameters may affect the production of a sustainable crop for the aquaculture industry under future climate change scenarios.